1980
DOI: 10.3758/bf03199594
|View full text |Cite
|
Sign up to set email alerts
|

Taste potentiates color-sickness associations in pigeons and quail

Abstract: The present experiments assessed cue utilization in pigeons and quail on similar tests of poison-based aversion learning. In Experiments 1 and 2, three groups of pigeons were given colored water, flavored water, or colored flavored water prior to induction of sickness; these experiments differed only as to the specific colors and flavors used as stimuli. In both experiments, the birds trained with flavored water exhibited reliable taste aversions when tested with uncolored flavored water. Similar degrees of av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
39
3

Year Published

1982
1982
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 7 publications
8
39
3
Order By: Relevance
“…However, identification of differences in selective pressures between species was by appeal to argument rather than by appeal to experimental evidence, and no attempt was made to identify the behavioral processes underlying species differences in behavior. As might be expected, subsequent research has cast doubt on the adequacy of ecological factors or unique learning mechanisms to account for the observed species differences (Gillette, Martin, & Bellingham, 1980;Lett, 1980).…”
Section: Comparisons Witb Otber Biological Approacbes To Tbe Study Ofmentioning
confidence: 98%
“…However, identification of differences in selective pressures between species was by appeal to argument rather than by appeal to experimental evidence, and no attempt was made to identify the behavioral processes underlying species differences in behavior. As might be expected, subsequent research has cast doubt on the adequacy of ecological factors or unique learning mechanisms to account for the observed species differences (Gillette, Martin, & Bellingham, 1980;Lett, 1980).…”
Section: Comparisons Witb Otber Biological Approacbes To Tbe Study Ofmentioning
confidence: 98%
“…Potentiation to a range of cues (e.g., odors, tastes, auditory cues, visual cues) within taste aversion conditioning has been reported since 1978 (e.g., Bouton, Dunlap, & Swartzentruber, 1987;Ellins, Cramer, & Whitmore, 1985;Galef & Osborne, 1978;Holder & Garcia, 1987;Lett, 1980), but evidence of potentiation in more traditional classical conditioning preparations has been scarce. Recently, however, Urcelay and Miller (2009) were the first to demonstrate potentiation in Pavlovian fear conditioning.…”
mentioning
confidence: 99%
“…As a further factual difficulty for the early interpretations of overshadowing, more recent experiments have shown that more salient stimuli can, under some conditions, potentiate rather than overshadow conditioning to less salient stimuli (Durlach & Rescorla, 1980;Lett, 1980;Rusiniak, Hankins, Garcia, & Brett, 1979). Much of the recent interest in potentiation has involved the study of drug-induced aversions conditioned with odor-taste compounds.…”
mentioning
confidence: 99%